IMPLEMENTASI ALGORITMA KONTROL PROPORTIONAL INTEGRAL (PI) DC-DC FLYBACK CONVERTER MENGGUNAKAN ARDUINO NANO UNTUK FUEL CELL - Alkafi Dimitri Sukmana; Waru Djuriatno; Panca Mudjirahardjo (Jurnal Mahasiswa TEUB, 2023)
Energy plays a very important role in human life. Every year, the demand for energy needs continues to increase and the majority of energy generation uses fossil fuels. So an environmentally friendly energy source is needed. One of the environmentally friendly energy sources is fuel cells. Themain problem with fuel cells is that the output voltage is unstable and changes depending on the pressure, temperature, and use of the fuel cell's composition. So one of the electronic equipment that can increase and stabilize the output voltage in the fuel cell is needed, namely the Dc-Dc flyback converter using PI (Proportional Integral) Control. The use of a flyback converter with a designed PI control has a role to set the PWM on the flyback converter switch. In this study, the Implementation of the PI Control Algorithm on the Dc-Dc flyback converter used voltage feedback. The purpose of this study is to design and analyze the performance characteristics of the PI controller in stabilizing the output voltage of the flyback converter even though there are changes in load and input voltage. In this study, there were two tests on the design results, namely testing the response of the flyback converter on the open loop and the close loop which was given PI control with the direct synthesis method. The results showed that the flyback converter has been successfully created and is able to produce an output voltage of 2-3x from an input voltage of 24Vdc. The converter is capable of producing a voltage of 63.6 Vdc with a duty cycle of 50% with an efficiency of 83.57%. From the close loop test, there will be variations in input voltage and load, the flyback converter output voltage can be kept constant at 72 volts with steady state error and relatively small settling time values. Sothe performance of the PI controller with Dc-Dc flyback converter in regulating the dc-dc output voltage of the flyback conveterter can respond to changes in input voltage, load, and setpoint stably and effectively. DAFTAR PUSTAKA[1] International Energy Agency (IEA), “International Energy Agency (IEA)- Report,” 2018.[2] Idham F, Halimi S, dan Latifah S. 2009. Alternatif Baru Sumber Pembangkit Listrik dengan Menggunakan Sedimen Laut Tropika Melalui Teknologi Microbial Fuel Cell. Teknologi Hasil Perikanan Institut Pertanian Bogor.[3] I. A. Safitri dkk., “UJI KINERJA SMART GRID FUEL CELL TIPE PROTON EXCHANGE MEMBRANE (PEM) DENGAN PENAMBAHANHIDROGEN,” 2016.[4] S. K. Rajasekaran, G. Uma, and K. Vijayakumar, "Design of Flyback Converter with PI Controller for Power Factor Correction,"International Journal of Engineering and Technology, vol. 8, no. 3, pp. 1216-1223, 2016.[5] Erni, Y. (2019). Sistem Kontrol. Bandung: Informatika.[6] Erni, Y. (2021). Sistem Kontrol Lanjut. Bandung: Informatika.[7] Ogata, K. (2010). Modern Control Engineering. New Jersey: Prentice Hall.